A potential role for interleukin-33 and γ-epithelium sodium channel in the pathogenesis of human malaria associated lung injury. (December 2015) - Ampawong, Sumate; Chaisri, Urai; Viriyavejakul, Parnpen; Prapansilp, Panote; Grau, Georges; Turner, Gareth; Pongponratn, Emsri
Abstract Background The pathogenesis of pulmonary oedema (PE) in patients with severe malaria is still unclear. It has been hypothesized that lung injury depends, in addition to microvascular obstruction, on an increased pulmonary capillary pressure and altered alveolar-capillary membrane permeability, causing pulmonary fluid accumulation. Methods This study compared the histopathological features of lung injury in Southeast Asian patients (n = 43) who died from severePlasmodium falciparum malaria, and correlated these with clinical history in groups with or without PE. To investigate the expression of mediators that may influence fluid accumulation in PE, immunohistochemistry and image analysis were performed on controls and sub-sets of patient with or without PE. Results The expression of leukocyte sub-set antigens, bronchial interleukin (IL)-33, γ-epithelium sodium channel (ENaC), aquaporin (AQP)-1 and -5, and control cytokeratin staining was quantified in the lung tissue of severe malaria patients. Bronchial IL-33 expression was significantly increased in severe malaria patients with PE. Malaria patients with shock showed significantly increased bronchial IL-33 compare to other clinical manifestations. Bronchial IL-33 levels were positively correlated with CD68+ monocyte and elastase + neutrophil, septal congestion and hyaline membrane formation. Moreover, the expression of both vascular smooth muscle cell (VSMC) and bronchial γ-ENaC significantly decreased in severe malaria patients with PE. Both VSMC and bronchial γ-ENaC were negatively correlated with the degree of parasitized erythrocyte sequestration, alveolar thickness, alveolar expansion score, septal congestion score, and malarial pigment score. In contrast AQP-1 and -5 and pan cytokeratin levels were similar between groups. Conclusions The results suggest that IL-33 may play a role in lung injury during severe malaria and lead to PE. Both VSMC and bronchial γ-ENaC downregulation may explain pulmonary fluid disturbances and participate in PE pathogenesis in severe malaria patients.